2010
DOI: 10.1096/fj.09-144766
|View full text |Cite
|
Sign up to set email alerts
|

Two cutinase‐like proteins secreted byMycobacterium tuberculosisshow very different lipolytic activities reflecting their physiological function

Abstract: Cutinases are extracellular enzymes that are able to degrade cutin, a polyester protecting plant leaves and many kinds of lipids. Although cutinases are mainly found in phytopathogenic fungi or bacteria, 7 genes related to the cutinase family have been predicted in the genome of Mycobacterium tuberculosis. These genes may encode proteins that are involved in the complex lipid metabolism of the bacterium. Here, we report on the biochemical characterization of two secreted proteins of M. tuberculosis, Rv1984c an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 43 publications
4
76
0
Order By: Relevance
“…2D). Seven cutinase-like proteins, with esterase activities in some of them, have been described in M. tuberculosis (42,51), and we suggest that one or more of these behaves similarly to Msmeg_1529, although none has yet been shown to cleave either TDM or mAGP. Rv3452, designated Culp4, is the closest relative of Msmeg_1529, has a putative signal peptide, and has been reported to be cell wallassociated (52).…”
Section: Discussionmentioning
confidence: 74%
“…2D). Seven cutinase-like proteins, with esterase activities in some of them, have been described in M. tuberculosis (42,51), and we suggest that one or more of these behaves similarly to Msmeg_1529, although none has yet been shown to cleave either TDM or mAGP. Rv3452, designated Culp4, is the closest relative of Msmeg_1529, has a putative signal peptide, and has been reported to be cell wallassociated (52).…”
Section: Discussionmentioning
confidence: 74%
“…In one case, two variants differed in an IS6110 sequence located in or absent from Rv1758. An IS6110 copy in the same sequence has also been found in strain H37Rv, and it has been reported that it might have a dual impact: on the expression of both cutinase, an enzyme involved in the lipid metabolism (27), and phospholipase plcD (16), an enzyme considered a virulence factor in certain studies (24). For the second case infected with clonal variants who was analyzed, we detected an IS6110 copy either present or absent in a region coding for the protein PPE34, which has recently been found to facilitate a shift toward the Th2 immune response, aiding the immune evasion by mycobacteria (7).…”
Section: Discussionmentioning
confidence: 90%
“…Such phospholipase activities have been identified in M. tuberculosis. Schué et al (28) isolated two secreted cutinases-like proteins: Rv1984c, which preferentially hydrolyzed medium-chain carboxylic esters and monoacylglycerols, and Rv3452, which behaved like a phospholipase A2. The other lipases/cutinases are most likely cell-wall-associated and surface-exposed (29).…”
Section: Resultsmentioning
confidence: 99%